2018
DOI: 10.1186/s12880-018-0255-7
|View full text |Cite
|
Sign up to set email alerts
|

An automated algorithm for the detection of cortical interruptions and its underlying loss of trabecular bone; a reproducibility study

Abstract: BackgroundWe developed a semi-automated algorithm that detects cortical interruptions in finger joints using high-resolution peripheral quantitative computed tomography (HR-pQCT), and extended it with trabecular void volume measurement. In this study we tested the reproducibility of the algorithm using scan/re-scan data.MethodsSecond and third metacarpophalangeal joints of 21 subjects (mean age 49 (SD 11) years, 17 early rheumatoid arthritis and 4 undifferentiated arthritis, all diagnosed < 1 year ago) were im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…However, manual scoring is laborious and requires substantial training and standardization. An automated detection algorithm has been developed, named the Cortical Interruption Detection Algorithm (39,40,52,53,64). The Cortical Interruption Detection Algorithm detects the presence of cortical interruptions, directing the reader to lesion locations to verify that they meet the erosion definition as opposed to those that merely represent physiological breaks in the cortical bone, i.e., vascular channels ( Figure 4A) or stack misalignment ( Figure 4B) and osteophyte formation ( Figure 4C).…”
Section: Erosion Detection By Hr-pqctmentioning
confidence: 99%
See 2 more Smart Citations
“…However, manual scoring is laborious and requires substantial training and standardization. An automated detection algorithm has been developed, named the Cortical Interruption Detection Algorithm (39,40,52,53,64). The Cortical Interruption Detection Algorithm detects the presence of cortical interruptions, directing the reader to lesion locations to verify that they meet the erosion definition as opposed to those that merely represent physiological breaks in the cortical bone, i.e., vascular channels ( Figure 4A) or stack misalignment ( Figure 4B) and osteophyte formation ( Figure 4C).…”
Section: Erosion Detection By Hr-pqctmentioning
confidence: 99%
“…Forty-six publications characterizing erosions or cortical breaks/interruptions were found. Erosions have been assessed in a variety of arthritic conditions including early inflammatory arthritis ( 3 , 33 , 37 , 53 , 58 , 59 , 67 ), RA ( 1 , 3 7 , 9 , 10 , 12 , 15 , 23 , 26 , 28 30 , 34 , 39 , 40 , 44 , 46 48 , 52 , 54 , 55 , 61 , 64 , 65 , 67 ), PsA ( 5 , 7 , 14 , 49 , 61 , 66 , 69 ), and erosive hand OA ( 21 ), as well as healthy controls ( 3 , 5 , 7 , 16 , 33 , 39 , 40 , 44 , 45 , 52 , 54 , 55 , 60 , 61 , 64 , 67 ) and subjects with ACPA antibodies but no features of arthritis ( 32 , 50 , 62 ).…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…HR-pQCT allows for the resolution of individual trabeculae (4), and the ability to quantitatively evaluate joint properties. Semi-automated techniques have been developed to assess periarticular bone mineral density and microarchitecture, joint space width as well as erosion volume (5)(6)(7)(8). An overview of these techniques is provided in a review by Klose-Jensen et al (9) in this special issue.…”
Section: Multi-modal Imaging: Utilizing Each Individual Imaging Modalmentioning
confidence: 99%
“…The high spatial resolution provided by HR-pQCT enables the analysis and quantification of small erosions, which are clinically significant as it has been shown that patients with RA have a greater number of small erosions compared to healthy controls [8], and have shown to have an association with pain and decreases in function [9]. Erosion volume has been calculated using manual, semi-automated and fully-automated tools with high reproducibility [10][11][12].…”
Section: Introductionmentioning
confidence: 99%